FROM THE MONOTECHNICAL WORKER TO THE POLYTECHNICAL WORKER: GLOBALIZATION AND PROFESSIONAL CHALLENGES (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The worldwide technological revolution brings with it a broader set of socio-economic, geopolitical and demographic factors that interact in multiple dimensions and intensify each othe. As entire industries adjust to the new technological era, most occupations are undergoing sudden transformations, pointing to a new profile of industrial worker. In today's digital knowledge society, new forms of work are appearing, eliminating the classic prototype of the Fordist worker. Monotechnical work does not fit in with the dynamic vision of the Fourth Industrial Revolution, nor with the dynamics of the net growth of jobs and skills. The profile of the Industry 4.0 worker is made up of versatility, decision-making and initiative, cooperation, autonomy, responsibility, creativity and effective participation in the production process. Considering the new work morphologies and the social unfolding immersed in and fascinated by Industry 4.0, this study aims to analyze the transition from the mono-technical worker to the multi-skilled worker supported by the processes of globalization and development. We will also examine the professional challenges facing this new generation of multi-skilled workers, their cognitive abilities and the needs generated by the new era of digital capital. To this end, we will use the historical dialectical method, through bibliographical research and analysis of texts related to the species.